Faktor-Faktor Potensial dalam Adopsi Fintech Lending di Kota Batam - Shellyna Shellyna; Wisnu Yuwono (Universitas Winaya Mukti, 2022)
Peer-to-Peer (P2P) fintech services are increasingly popular in line with the government's tangible form and accelerated penetration of people who are not yet fully accessible by banking institutions. However, the acceptance of P2P technology by the public does not only depend on government regulations but also needs to understand its users' perspectives and knowledge so they can adapt to digital transformation in the financial services industry. This study aims to identify the potential factors that influence the attitude and adoption of fintech by P2P users in Batam City. The research sample was taken using the purposive sampling method, with a total sample that met the criteria of as many as 365 of the 422 respondents collected via Google form. All data were analyzed using the Smart PLS 3 program. The results prove that perceived usefulness, ease of use, risk, user innovativeness and government support significantly influence attitudes toward the intention to adopt fintech. Meanwhile, financial literacy does not affect users' attitudes toward adopting fintech. This research contributes to the literature on fintech adoption by expanding TAM and is expected to provide valuable insights.